Distribution and risk of the second discordant primary cancers combined after a specific first primary cancer in German and Swedish cancer registries. Issue 1 (1st December 2015) - Chen, Tianhui; Fallah, Mahdi; Jansen, Lina; Castro, Felipe A.; Krilavicuite, Agne; Katalinic, Alexander; Eisemann, Nora; Emrich, Katharina; Holleczek, Bernd; Geiss, Karla; Eberle, Andrea; Sundquist, Jan; et al.
Highlights We used huge databases (covering 27 million Germans and 9 million Swedes). We found elevated risk of SDPCs combined after 19 cancers in both countries. Our data suggest common etiology of SDPCs after most of first primary cancers. Our data suggest similar registration practices for most SDPCs in both countries. Decreased risk after fatal cancers in Germany may be due to reporting practices.